Effect of B4C and MOS2 reinforcement on micro structure and wear properties of aluminum hybrid composite for automotive applications. (1st November 2019) - Liu, Shoufa; Wang, Yinwei; Muthuramalingam, T.; Anbuchezhiyan, G.
Abstract: The utilization of particulate reinforced aluminium hybrid metal matrix composites is being increased in automotive applications due to its distinct properties. In the present study, an endeavour has been made to synthesize Al7075 aluminium alloy with reinforcement of B4 C and MoS2 as lubricant under various weight percentages of 4%, 8% and 12% using stir casting process. The compressive strength, tensile strength, hardness, micro structural analysis and tribological behavior of the synthesized hybrid composites have been analyzed and investigated. From the experimental investigation, it has been observed that the reinforcement particles are uniformly distributed in the matrix alloy as fine dendrites in alumnium solid solutions. The tensile strength, compressive strength, and hardness of the reinforced composites could be increased by adding the reinforcement compared to monolithic alloy. The significant improvement of wear resistance and coefficient of friction of aluminium hybrid composites has been achieved owing to inclusion of solid lubricant (MoS2 ) along with hard ceramic reinforcement particles (B4 C) in the matrix alloy. Highlights: The friction coefficient increases by the Inclusion of B4 C. The worn surface was smooth due to particulate micro fracture. The hardness of the hybrid composite increases with B4 C and MoS2 . The ultimate strength and yield tensile strength increases with B4 C and MoS2 .